2012
DOI: 10.1074/jbc.m112.428466
|View full text |Cite
|
Sign up to set email alerts
|

Human SMC2 Protein, a Core Subunit of Human Condensin Complex, Is a Novel Transcriptional Target of the WNT Signaling Pathway and a New Therapeutic Target

Abstract: Background: Condensin SMC proteins are frequently overexpressed in WNT-activated hyperplastic cells. Results:The SMC2 promoter is a novel target on the ␤-catenin⅐TCF4 transcription complex. Conclusion: ␤-Catenin⅐TCF4 may drive production of condensin in hyperplastic cells. SMC2 is required to ensure cellular mitosis and fast proliferation. Significance: Down-regulation of SMC2 expression can repress cell proliferation in WNT-activated cells and represents a new therapeutic target in cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 34 publications
1
62
0
Order By: Relevance
“…The structural maintenance of chromosomes protein-2 encoded by SMC2 is a core component of the condensin complex that is responsible for close packaging of chromatin before cell division (55). Moreover, SMC2 is a direct transcriptional target of oncogenic WNT signaling and N-Myc (56,57), and is emerging as a critical player in the DNA damage response (58). The index risk SNP at one of the seven new cross-cancer susceptibility loci discussed here was a genotyped SNP while at four other loci we were able to identify a genotyped SNP in the same region that was also genome-wide significant at P < 10 −8 .…”
Section: Discussionmentioning
confidence: 99%
“…The structural maintenance of chromosomes protein-2 encoded by SMC2 is a core component of the condensin complex that is responsible for close packaging of chromatin before cell division (55). Moreover, SMC2 is a direct transcriptional target of oncogenic WNT signaling and N-Myc (56,57), and is emerging as a critical player in the DNA damage response (58). The index risk SNP at one of the seven new cross-cancer susceptibility loci discussed here was a genotyped SNP while at four other loci we were able to identify a genotyped SNP in the same region that was also genome-wide significant at P < 10 −8 .…”
Section: Discussionmentioning
confidence: 99%
“…Cohesin mutations have been identified in myeloid leukemias (Leeke et al, 2014). The condensin component Smc2 and the Smc5/6 complex component Smc6 are overexpressed in cancers, such as colorectal, neuroblastoma and breast cancer (Davalos et al, 2012;Murakami-Tonami et al, 2014;Stevens et al, 2011). Furthermore, mutation of Smc5 is linked to the development of brain metastases (Saunus et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we found that SMC2 interacts with MYCN and is involved in transcriptional regulation of DDR genes, and that SMC2 expression is regulated by MYCN as well as by Wnt 54 (Fig. 6C).…”
Section: Discussionmentioning
confidence: 51%